(untitled) (Research, Society and Development, 2021)
This research describes the gene expression of molecules related to inflammation and bone metabolism in all patients submitted to dental implant surgery attended at a Brazilian institution. A convenience sample was collected over 2 years. The bone samples were processed for extraction of total RNA and reverse transcription of cDNA. Relative quantification by real-time polymerase chain reaction of target genes was performed. The sample was characterized demographically and according heath conditions. The patients were grouped. The control group was composed of 17 healthy patients, 6 patients were included in the antihypertensive therapy group, 3 were smokers, another 3 were smokers and were under antihypertensive treatment, and 3 were ex-smokers (smoked for 10 years but had quit for at least 5 years). The ex-smoker group presented the highest values, and the Hypertensive group presented the lowest values of Macrophage colony-stimulating factor, Osteonectin, Bone Morphogenetic Protein II, and Integrin. All smokers demonstrated expression values comparable to the Control group. The highest expression values of Osteopontin, RUNX, and Alkaline Phosphatase were observed in the Hypertensive and the Smoker group, while the lowest values were found in the Hypertensive group. Smokers, Ex-smokers, and the Control group demonstrated similar values. As conclusion, gene downregulation was observed in patients under anti-hypertensive therapy. Smoke seems to reduce expression of genes involve in bone formation and increase genes responsible for resorptive activity. This pattern of genic expression may be involved in higher implant loss, observed in smokers. Stop smoke seems to return expression of some of these genes.